2014
DOI: 10.1145/2666356.2594299
|View full text |Cite
|
Sign up to set email alerts
|

FlowDroid

Abstract: Today's smartphones are a ubiquitous source of private and confidential data. At the same time, smartphone users are plagued by carelessly programmed apps that leak important data by accident, and by malicious apps that exploit their given privileges to copy such data intentionally. While existing static taint-analysis approaches have the potential of detecting such data leaks ahead of time, all approaches for Android use a number of coarse-grain approximations that can yield high numbers of missed leaks and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 831 publications
(115 citation statements)
references
References 24 publications
0
72
0
3
Order By: Relevance
“…Static analysis-based approaches determine whether apps are malicious or benign, and consider the possibility of leakage of private data by analyzing the package files of apps without running them [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Static Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Static analysis-based approaches determine whether apps are malicious or benign, and consider the possibility of leakage of private data by analyzing the package files of apps without running them [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Static Analysismentioning
confidence: 99%
“…Yet another static approach based on a control flow graph (CFG) detects user privacy leaks through inter-component communication (ICC) [33][34][35]. A machine learning-based approach was recently proposed [36] that uses Extra-Trees, a machine learning algorithm to detect malicious apps regardless of code obfuscation.…”
Section: Static Analysismentioning
confidence: 99%
“…The majority of the calls use a specific string key to extract extra data from Intents whereas data type itself is encoded in the name of the methods. This research also attempted to use Flowdroid [10] for static analysis on more precise Intent structure, but it reported that the simple CFG-based analysis mentioned previously is enough for Intent fuzz testing in terms of scalability and precision [5]. A set of Intents was generated afterward with the statically analyzed Intent structure information, target components were executed with these fuzzed Intents, and both code coverage and crashes due to exceptions were monitored.…”
Section: Related Workmentioning
confidence: 99%
“…A mark * in the table tells this difference. Both IntentFuzzer [5] and ICCFuzzer [7] have used FlowDroid [10] for backend of their own static analyzer, for example, to collect keys and types of extra data of Intent statically. ICCFuzzer [7] went one step more to collect event handler information in Activity and Service components potentially to trigger deeper execution of target Android components, which a mark † points out.…”
Section: Comparison With Existing Intent Fuzzing Tools For Detecting mentioning
confidence: 99%
“…Since static analysis is very efficient at tracking data flow within an application, most of the static analysis tools for Android applications are focused on performing some kind of data flow analysis for example privacy leaks [7]- [9].…”
Section: Related Workmentioning
confidence: 99%